2021
DOI: 10.14218/jcth.2021.00013
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram Based on Perioperative Factors to Predict Post-hepatectomy Liver Failure

Abstract: Background and Aims: Post-hepatectomy liver failure (PHLF) is a severe complication and main cause of death in patients undergoing hepatectomy. The aim of this study was to build a predictive model of PHLF in patients undergoing hepatectomy. Methods: We retrospectively analyzed patients undergoing hepatectomy at Zhongshan Hospital, Fudan University from July 2015 to June 2018, and randomly divided them into development and internal validation cohorts. External validation was performed in an independent cohort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Patients with a perioperative PLT count< 150/nL (four studies, 817 patients; odds ratio [OR]: 4.79; 95% CI, 2.89-7.94) and those with a PLT count< 100/nL (four studies, 949 patients; OR: 4.65; 95% CI: 2.608.31) had a high risk of developing PHLF ( 37 ). As shown in previous studies, PLT count ( 38 ), age ( 39 ), Cr ( 40 ), INR ( 41 ), and AFP ( 42 ) are all predictors of PHLF.…”
Section: Discussionsupporting
confidence: 63%
“…Patients with a perioperative PLT count< 150/nL (four studies, 817 patients; odds ratio [OR]: 4.79; 95% CI, 2.89-7.94) and those with a PLT count< 100/nL (four studies, 949 patients; OR: 4.65; 95% CI: 2.608.31) had a high risk of developing PHLF ( 37 ). As shown in previous studies, PLT count ( 38 ), age ( 39 ), Cr ( 40 ), INR ( 41 ), and AFP ( 42 ) are all predictors of PHLF.…”
Section: Discussionsupporting
confidence: 63%
“…At the time of this study, there are many predictive models for surgical treatment, radiotherapy, and chemotherapy of ALD [ 36 , 37 ], but there is a lack of predictive models for medical treatment of ALD patients. This study included most of the baseline indicators that were found to be meaningful in previous studies and constructed a nomogram using the variables of relapse, cirrhosis, cancer, and an MELD score of ≥21.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several models were established to predict PHLF but exhibited obvious heterogeneity. Some nomograms were derived from data of patients with benign and malignant lesions ( 15 ), while some nomograms incorporated both preoperative and intraoperative variables ( 15 , 25 ), and some nomograms were based on analysis of both minor and major hepatectomies ( 17 , 18 , 26 ). Recently, Chin and colleagues ( 27 ) created a PHLF prognostic nomogram for major hepatectomy; however, the study involved patients with either HCC or colorectal liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few predictive models have been established for PHLF in HCC patients and showed certain predictive ability (15)(16)(17)(18)(19). However, most of these models incorporated both preand postoperative predictors which might reduce the validity of preoperative prediction.…”
Section: Introductionmentioning
confidence: 99%